1994
DOI: 10.1016/0168-9002(94)90233-x
|View full text |Cite
|
Sign up to set email alerts
|

Present status of undoped semi-insulating LEC bulk GaAs as a radiation spectrometer

Abstract: Bulk GaAs has undergone extensive research by several groups in order to ascertain its usefulness as a room temperature radiation spectrometer. The results of an experimental program studying the properties of detectors fabricated from bulk GaAs are summarized in this paper. Electric field models of the active region are compared with measured results. Limitations of bulk LEC GaAs as a material for radiation spectrometers are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…[2,3]) in terms of the ionisation of deep levels such as EL2. A recently published model by McGregor et al [4] which includes a field-enhanced capture rate produces field distributions which are in agreement with our data reported in reference [1].…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…[2,3]) in terms of the ionisation of deep levels such as EL2. A recently published model by McGregor et al [4] which includes a field-enhanced capture rate produces field distributions which are in agreement with our data reported in reference [1].…”
Section: Introductionsupporting
confidence: 92%
“…For comparison, figure 5 shows similar data calculated using equal values of the electron and hole mean lifetimes of 10ns [4]. In this case the slower hole drift velocity causes the holes' mean drift length to be less than that of the electrons and the CCE decreases towards the rear of the detector as the contribution from the hole current increases.…”
Section: B Gamma Radiationmentioning
confidence: 68%
“…In fact it has been theoretically [9,10] and experimentally [4,5, 11,12] shown that in SI LEC bulk GaAs detectors two different regions are present: a high field region, near the Schottky contact, and a low field region, near the ohmic contact.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments [3][4][5][6][7][8][9] that use the electro-optic Pockels effect in order to measure the local electric fields in the sample have opened up the way towards a more detailed quantitative understanding of the domains and the trapping process in SI GaAs. There is a considerable interest in the properties of the EL2 defect because SI GaAs has an increasing relevance, e.g., as a particle detector [10][11][12][13] and for optical data storage. 14 The reader may well wonder why the transport properties of SI GaAs should be of any particular interest.…”
Section: Introductionmentioning
confidence: 99%